Modeling and control of a self-contained trailer system - Medina Medina, Wilder (2018)
A solution is proposed by means of a trailer-type mobile robot control system applied to a company in charge of transporting material, demonstrating that it is an applicable and viable solution. A mathematical model was defined, involving the integration of two control techniques: linear quadratic regulator (LQR) and fuzzy logic. Favorable results of the trajectory control and tracking system are shown, pointing out the improvements achieved when integrating both control techniques and the ability of the system to respond correctly to guide the robot by any type of trajectory.